2001
DOI: 10.1254/jjp.85.95
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Concanavalin A-Induced Mice Hepatitis by Coumarin Derivatives

Abstract: ABSTRACT-The effects of coumarin derivatives, osthole, imperatorin, Pd-Ia, Pd-II and Pd-III, on mice concanavalin A (Con A) (0.2 mg/mouse, i.v.)-induced hepatitis were studied. At the dose of 200 mg/ kg (i.p.), these coumarins inhibited more than 90% of the Con A-induced elevation of plasma alanine aminotransferase activity, but glycyrrhizin (200 mg / kg, i.p.) caused only 45% inhibition. At the dose of 100 mg/ kg (i.p.), osthole produced the strongest inhibition among these coumarins. The inhibitory activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…Osthole has long been used for the treatment of eczema, cutaneous pruritus, trichomonas vaginalis infection, and sexual dysfunction. Recent studies have revealed that Osthole may have anti-inflammatory [6], vasorelaxant [7], and antiallergic [8] effects, as well as the prophylactic effects in hepatitis [9]. In addition, Osthole, as widely reported, exhibits an anti-cancer effect by suppressing cancer cell growth and enhancing apoptosis [10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Osthole has long been used for the treatment of eczema, cutaneous pruritus, trichomonas vaginalis infection, and sexual dysfunction. Recent studies have revealed that Osthole may have anti-inflammatory [6], vasorelaxant [7], and antiallergic [8] effects, as well as the prophylactic effects in hepatitis [9]. In addition, Osthole, as widely reported, exhibits an anti-cancer effect by suppressing cancer cell growth and enhancing apoptosis [10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Coumarin derivatives are active components of herbal medicine and are known not to exhibit cellular toxicity. In the present study, the coumarins' doses were arranged according to the previous studies [32,38]. Direct evidence of oxidative stress was noted in the occurrence of alterations in various hepatic parameters decreased activities of antioxidant enzymes CAT, SOD and increased MDA levels in CCl 4 applied group in comparison to control.…”
Section: Discussionmentioning
confidence: 91%
“…In Con A-induced hepatitis, osthole, imperatorin, pd-Ia, pd-II and pd-III show stronger effects than glycyrrhizin to decrease Con A-induced elevation of plasma ALT. Furthermore, a morphological study also showed the effectiveness of these coumarins (not shown) (18). Of these coumarins, osthole and imperatorin have the strongest protective effects.…”
Section: Coumarinsmentioning
confidence: 94%
“…Of these coumarins, osthole and imperatorin have the strongest protective effects. Osthenol is an osthole derivative with substitution of a 7-methoxy group for the 7-hydroxy of osthole, whereby it loses its protective effect (18). Thus, the 7-methoxy group of osthole plays an important role in protecting the liver against injury.…”
Section: Coumarinsmentioning
confidence: 99%
See 1 more Smart Citation